A method for optimizing the edge thickness of a battery electrode sheet
Patent Information
- Application Number
- CN202510539760.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2026-10-27
AI Technical Summary
[0010]由以上本发明提供的技术方案可见,与现有技术相比较,本发明提供了一种电池极片边缘厚度的优化处理方法,其设计科学,能够有效消除电池极片的边缘部分(即边缘料区)存在的厚度过大区域,避免极片边缘超厚(即厚度过大),可靠地控制电池极片的边缘厚度,避免出现电池极片的边缘厚度异常问题(即边缘超厚,厚度过大),显著提升电池极片的生产质量,具有重大的实践意义。
Smart Images

Figure CN122991966A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a method for optimizing the edge thickness of battery electrodes. Background Technology
[0002] Lithium-ion batteries have been widely used in digital products, electric vehicles and energy storage due to their advantages such as high energy density, good cycle performance and being green and pollution-free.
[0003] Currently, in the process of preparing lithium battery electrodes, a slurry coating is applied to the surface of the elongated current collector 1 to form a slurry coating 2. The slurry coating 2 includes an edge area 21 and a normal area (i.e., a central area) 22. Due to the fluid characteristics of the slurry, see [reference needed]. Figure 1a As shown, semi-circular raised edge material areas 21 are easily formed at the starting point, ending point, and both sides of the slurry coating 2. In other words, during the coating process, the edge of the battery electrode is prone to a "thick edge" phenomenon, that is, the edge thickness of the electrode is too large, which is abnormal: the edge thickness of the slurry coating is several micrometers or even tens of micrometers thicker than the normal area (e.g., the central area). Then, during the drying and winding process after coating, due to the superposition of multiple electrode layers, the edge of the electrode roll will be too thick. In severe cases, it may even cause the battery electrode to bulge or even break during winding.
[0004] In addition, excessively thick battery electrode edges can lead to over-pressure on the edges of the coated and dried electrode during the rolling process, resulting in abnormalities such as electrode sticking to the rollers and lithium deposition at the battery edges.
[0005] Therefore, there is an urgent need to develop a technology that can solve the above-mentioned technical problems. Summary of the Invention
[0006] The purpose of this invention is to address the technical deficiencies of existing technologies by providing an optimized method for processing the edge thickness of battery electrode sheets.
[0007] Therefore, the present invention provides a method for optimizing the edge thickness of battery electrode sheets, which includes the following steps:
[0008] Step S1, test the thickness difference of the battery electrode: For the battery electrode after the slurry coating and drying are completed, test the thickness of the edge material area and the thickness of the normal material area of the battery electrode to obtain the thickness difference of the battery electrode.
[0009] Step S2, perform powder removal operation on the battery electrode sheet: First, use a laser to remove the powder from the edge area of the battery electrode sheet. Then, use a rotating brush roller to rub the edge area of the battery electrode sheet to continue removing the powder from the edge area, so as to obtain a battery electrode sheet with qualified edge thickness.
[0010] As can be seen from the technical solution provided by the present invention above, compared with the prior art, the present invention provides an optimized processing method for the edge thickness of battery electrode sheets. Its design is scientific and can effectively eliminate the excessively thick area in the edge part (i.e., edge material area) of the battery electrode sheet, avoid the electrode sheet edge being too thick (i.e., excessive thickness), reliably control the edge thickness of the battery electrode sheet, avoid the problem of abnormal edge thickness of the battery electrode sheet (i.e., excessive edge thickness), significantly improve the production quality of battery electrode sheets, and has significant practical significance.
[0011] By applying this invention, the amount of "thinning" of the battery electrode edge thickness can be precisely controlled, ensuring the consistency of the surface density of the active material in the electrode edge and the middle part of the battery electrode. Attached Figure Description
[0012] Figure 1a This is a schematic diagram of a battery electrode sheet after coating and drying, where the solution of the present invention has not been applied.
[0013] Figure 1b This is a schematic diagram of a coated and dried battery electrode sheet after laser removal (i.e., cutting, thinning) using the optimized edge thickness processing method for battery electrode sheets provided by this invention.
[0014] Figure 2 A flowchart illustrating a method for optimizing the edge thickness of battery electrode sheets provided by the present invention;
[0015] Figure 3a A front view of the positional relationship between the infrared detector and the battery electrode, based on a method for optimizing the edge thickness of a battery electrode according to the present invention.
[0016] Figure 3b A front view of the positional relationship between a continuous laser (as a laser source) and a battery electrode sheet, provided by the present invention, for an optimization method of the edge thickness of a battery electrode sheet.
[0017] Figure 3c A front view of the positional relationship between a brush roller and a battery electrode sheet, based on a method for optimizing the edge thickness of a battery electrode sheet according to the present invention.
[0018] Figure 4The left view shows the positional relationship between the infrared detector, the continuous laser (as a laser source), and the brush roller and the battery electrode, based on the method for optimizing the edge thickness of a battery electrode according to the present invention.
[0019] In the figure, 1 is the battery electrode current collector, 2 is the slurry coating, 21 is the edge material area, 22 is the normal material area, 3 is the mounting bracket, 4 is the infrared detector, 5 is the continuous laser, and 6 is the brush roller. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," and "counterclockwise," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.
[0022] In the description of this patent, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "setting" should be interpreted broadly. For example, they can refer to a fixed connection or setting, a detachable connection or setting, or an integral connection or setting. Those skilled in the art can understand the specific meaning of the above terms in this patent according to the specific circumstances.
[0023] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.
[0024] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0025] See Figure 1b , Figure 2 , Figures 3a to 3b , Figure 4 This invention provides a method for optimizing the edge thickness of battery electrode sheets, comprising the following steps:
[0026] Step S1, test the thickness difference of the battery electrode: For the battery electrode after the slurry coating and drying are completed, test the thickness of the edge material area (i.e., edge thickness) and the thickness of the normal material area (e.g., the thickness of the middle area, which is a qualified thickness) of the battery electrode to obtain the thickness difference of the battery electrode.
[0027] It should be noted that the thickness difference of the battery electrode sheet is the difference between the thickness of the edge material area and the thickness of the normal material area of the battery electrode sheet immediately after the slurry coating and drying are completed.
[0028] Step S2, perform powder removal operation on the battery electrode sheet: First, use a laser to remove the powder from the edge area of the battery electrode sheet (i.e., cut and thin it), and then use a rotating brush roller to rub the edge area of the battery electrode sheet to continue the powder removal operation on the edge area of the battery electrode sheet, so as to obtain a battery electrode sheet with qualified edge area thickness.
[0029] In this invention, specifically, for battery electrodes obtained by continuous coating, the edge material area of the battery electrode is the material area (with a preset width) on the left and right edge parts of the battery electrode slurry coating.
[0030] For battery electrodes obtained by intermittent coating, the edge material area of the battery electrode is the material area (the width can be preset) at the beginning of the battery electrode slurry coating.
[0031] In this invention, specifically, the laser is a continuous laser output from a continuous laser 5.
[0032] In this invention, for specific implementation, see [link to relevant documentation]. Figure 3b As shown, for battery electrodes obtained by continuous coating, two continuous lasers 5 are set directly above the edge material areas (i.e., the two side edges) on the left and right sides of the battery electrode.
[0033] Furthermore, the continuous laser 5 is positioned at the bottom of the mounting bracket 3.
[0034] In this invention, for specific implementation, see [link to relevant documentation]. Figure 3c As shown, a brush roller 6 is provided directly above the battery electrode;
[0035] In practice, the central axis of the brush roller 6 is perpendicular to the straight line containing the long side of the battery electrode.
[0036] In practice, when the battery electrode is in motion, the rotation direction of the brush roller 6 is tangent to the moving direction of the battery electrode (i.e., the direction in which it moves with the conveyor belt, i.e., the belt carrying direction).
[0037] In practice, the brush roller 6 is a conventional mechanical device that can be a brush roller with vacuum dust removal function.
[0038] It should be noted that, in practice, the brush roller 6 is linked to a drive device (e.g., connected to the output shaft of a motor via a coupling), and rotates accordingly under the drive of the drive device. Of course, there is also a corresponding support frame to support all the components of the entire device. The aforementioned drive device, support frame, etc., are common structures and will not be described in detail here.
[0039] It should be noted that, see Figure 3c As shown, in this invention, both ends of the brush roller 6 can be connected to the bottom of the mounting bracket 3 via a connecting swing shaft 7, and the two connecting swing shafts 7 are arranged parallel to each other; therefore, the distance and pressure between the brush roller 6 and the battery electrode below can be adjusted by adjusting the tilt angle of the two connecting swing shafts 7 (i.e., the angle between them and the horizontal vertical plane).
[0040] In this invention, specifically, the battery electrode sheet after the slurry coating and drying are in a state including a static state and a dynamic state (e.g., being conveyed by a conveyor belt, i.e., during normal belt movement, when the battery electrode sheet is placed on top of the conveyor belt).
[0041] In specific implementation, the method of the present invention includes the following working mode one and working mode two:
[0042] Work Mode 1:
[0043] When the battery electrode is in a static state, step S1 specifically includes the following step S11, and step S2 specifically includes the following step S12.
[0044] Step S11, test the static thickness difference of the battery electrode: For the battery electrode in a static state after the slurry coating and drying are completed, test the thickness of the edge material area (i.e., edge thickness) and the thickness of the normal material area (e.g., the thickness of the middle area) of the battery electrode to obtain the first static thickness difference ΔT of the battery electrode.
[0045] It should be noted that the static thickness difference ΔT of the battery electrode sheet is the difference between the thickness of the edge material area and the thickness of the normal material area of the battery electrode sheet in the static state (i.e., static) immediately after the slurry coating and drying are completed.
[0046] In this invention, specifically in step S11, for the battery electrode sheet after the slurry coating and drying are completed, when it is in a static state (i.e., stationary), a micrometer is used to measure the static thickness of the battery electrode sheet, and the edge material area thickness (i.e., edge thickness) T0 and the normal material area thickness (e.g., the thickness of the middle area) T1 of the battery electrode sheet are measured before the powder removal operation.
[0047] Among them, the first static thickness difference of the battery electrode ΔT = T0 - T1 is the thickness of the powder on the battery electrode (i.e. the coating of active material on the electrode) that needs to be removed, which is also the thickness of the extra-thick part of the edge material area (the part that exceeds the thickness of the normal material area).
[0048] Step S12, static material removal operation of battery electrode sheet: First, the material powder in the edge area of the battery electrode sheet in a static state is removed (i.e., cut) by laser. Then, the edge area of the battery electrode sheet is rubbed by rotating brush roller to continue the material removal operation in the edge area of the battery electrode sheet until the battery electrode sheet meets the first condition and the second condition at the same time (i.e., stop rotating the brush roller), so as to obtain a battery electrode sheet with qualified edge material thickness.
[0049] The first condition is: the heat-affected areas on the edge material area that have been removed due to the laser removal (cutting) operation;
[0050] The second condition is: the second static thickness difference ΔT' of the battery electrode sheet is less than or equal to the preset static thickness qualified difference (that is, the brush roller also continues to remove the powder in the edge material area that exceeds the normal material area thickness at the same time).
[0051] The second static thickness difference ΔT' of the battery electrode is equal to the absolute value of the difference between the edge material area thickness (i.e., edge thickness) T0' and the normal material area thickness (e.g., central area thickness) T1' of the battery electrode after the material powder removal operation by laser and brush roller.
[0052] Among them, the second static thickness difference of the battery electrode is ΔT'=|T0'-T1'|.
[0053] In this invention, for specific implementation, see [link to relevant documentation]. Figure 1b As shown, after using a laser to remove (i.e., cut) the powder in the edge area of a stationary battery electrode, the powder distribution of the battery electrode is as follows. Figure 1b As shown. For the edge material area after laser cleaning, its upper part is similar to a crescent shape, and the central area has less material powder. The cleaning depth of the central area irradiated by the laser is deeper than that of the two sides.
[0054] In this invention, specifically, the preset range of the static thickness acceptable difference is 0 to 3 μm, preferably 3 μm or 2 μm.
[0055] In this invention, it should be noted that during the laser removal (cutting) of the edge material area of the battery electrode, the powder area near the cut is heated, which may cause changes in the powder structure, forming a heat-affected zone (i.e., a heat-affected area). The presence of the heat-affected zone affects the smoothness of the surface of the edge material area of the battery electrode, and may even cause phenomena such as indentation. Therefore, it is necessary to further employ a brush roller to continue the powder removal operation to remove the heat-affected zone (i.e., the heat-affected area) formed on the battery electrode due to the laser removal operation.
[0056] It should be noted that after continuous energy input from a laser to the edge material area of the battery electrode, significant heat accumulation will occur, forming a heat-affected zone. In this case, it is necessary to remove the heat-affected zone using a brush roller.
[0057] In this invention, specifically in step S12, when the laser is used to remove (i.e., cut) the powder in the edge area of the battery electrode sheet in a static state, the thickness of the powder removed by the laser ranges from 20% to 60%ΔT. That is, the height of the edge area removed by the laser is 20%-60% of the thickness of the excessively thick portion of the edge area.
[0058] In specific implementation, in step S12, the thickness of the powder eliminated by the brush roller is in the range of 40 to 80% ΔT.
[0059] It should be noted that the reason why the laser cleaning thickness (i.e. the thickness of the powder removed by the laser) is selected as 20%-60% for this invention is that if the laser cleaning thickness is less than 20%, it will be difficult for the brush roller to remove the remaining powder; if the cleaning thickness is greater than 60%, it will cause the laser to clean the powder too deeply in the center, resulting in point-like lithium plating in local areas of the battery electrode during charging and discharging.
[0060] It should be noted that, in this invention, the use of a brush roller to clean the powder is primarily to reduce the central impact caused by laser cleaning alone. Due to the inherent properties of the laser, the central area of the material zone at the edge of the battery electrode after laser irradiation will have a deeper cleaning depth than the sides, resulting in less powder in the central area. (See [link to previous section]). Figure 1b As shown, a laser alone cannot be used to remove excess powder. In this invention, after removing excess powder from the electrode using a brush roller, the electrode becomes flatter, avoiding the problem of insufficient powder in the central area during laser cleaning. The removal ratio of the brush roller (i.e., the thickness of powder removed by the brush roller) is mainly due to the characteristics of the brush roller. Without the initial laser cleaning to disrupt the edge powder area, the brush roller cannot remove excess powder.
[0061] It should be noted that, for the present invention, when the first static thickness difference ΔT of the battery electrode is large, the thickness of the part that needs to be cut off by laser is relatively large. In this case, the output power of the continuous laser used to output the laser should be increased accordingly.
[0062] In this invention, specifically in step S12, the second static thickness difference ΔT' of the battery electrode is ≤3μm.
[0063] In this invention, specifically in step S12, if the second static thickness difference ΔT' of the battery electrode is greater than the preset static thickness acceptable difference (e.g., 3 μm), then the pressure applied by the brush roller to the battery electrode (e.g., the vertical downward pressure applied to the battery electrode directly below) is increased, and the gap between the roller body of the brush roller (with bristles evenly distributed on the roller body) and the surface of the battery electrode is reduced (i.e., the spacing) until the battery electrode simultaneously meets the first condition and the second condition.
[0064] It should be noted that when the battery electrode is in a static state, if the thickness difference between the edge and the middle (the second static thickness difference ΔT' of the battery electrode) is greater than the preset static thickness acceptable difference (e.g., 3μm) after the powder cleaning operation, it proves that the edge cleaning ability is insufficient. It is necessary to further increase the pressure between the brush roller and the electrode and reduce the gap between the roller body (with bristles evenly distributed on the roller body) and the surface of the battery electrode (i.e., the spacing) in order to further increase the brush roller's ability to remove powder from the material area.
[0065] Working Mode Two:
[0066] When the battery electrode is in a dynamic state (e.g., being conveyed by a conveyor belt), step S1 specifically includes the following step S21, and step S2 specifically includes the following step S22.
[0067] Step S21, test the dynamic thickness difference of the battery electrode: For battery electrodes that are in a dynamic state (e.g., being conveyed by a conveyor belt) after slurry coating and drying, test the thickness of the edge material area (i.e., edge thickness) and the thickness of the normal material area (e.g., the thickness of the middle area) of the battery electrode to obtain the first dynamic thickness difference ΔT of the battery electrode. 动 ;
[0068] It should be noted that the dynamic thickness difference ΔT of the battery electrode sheets 动 This refers to the difference between the thickness of the edge material area and the thickness of the normal material area of a battery electrode sheet that has just completed slurry coating and drying, under dynamic conditions.
[0069] In this invention, specifically in step S21, for the battery electrode sheet after slurry coating and drying, when it is in a dynamic state (e.g., being conveyed by a conveyor belt), an infrared detector (e.g., a laser thickness gauge) is used to perform static thickness measurement on the battery electrode sheet, measuring the edge material area thickness (i.e., edge thickness) T of the battery electrode sheet before the powder removal operation. 动0 And the thickness of the normal material zone (e.g., the thickness of the middle area) T 动1 ;
[0070] Among them, the first dynamic thickness difference ΔT of the battery electrode 动 =T 动0 -T 动1 This refers to the thickness of the powder material (i.e., the active material coating) on the battery electrode that needs to be removed, which is also the thickness of the extra-thick part of the edge material area.
[0071] For specific implementation details, see [link to implementation details]. Figure 3a , Figure 4 As shown, for continuously coated battery electrodes, an infrared detector 4 is placed directly above the lateral center of the battery electrode.
[0072] Two additional infrared detectors 4 are installed directly above the edge material areas (i.e., the two side edges) on the left and right sides of the battery electrode sheet.
[0073] Furthermore, the infrared detector 4 (specifically a laser thickness gauge) is located at the bottom of the mounting bracket 3.
[0074] It should be noted that the infrared detector 4 is a conventional measuring device. For this invention, the infrared detector 4 can specifically be a laser thickness gauge, model DC-EL-LS-700, manufactured by Shenzhen Dacheng Precision Equipment Co., Ltd., but is not limited to this model. It is only necessary to be able to perform the functions required by this invention. All infrared detectors used in this invention are laser thickness gauges (this embodiment uses a laser thickness gauge, but other thickness measurement methods are also feasible, such as X-ray detection. The detector plays a detection feedback role in this invention).
[0075] Step S22, perform dynamic powder removal operation on the battery electrode sheet: First, use a laser to remove (i.e. cut) the powder in the edge area of the battery electrode sheet under dynamic conditions. Then, use a rotating brush roller to rub the edge area of the battery electrode sheet to continue the powder removal operation until the battery electrode sheet meets the third and fourth conditions at the same time (i.e., stop rotating the brush roller), thereby obtaining a battery electrode sheet with qualified edge area thickness.
[0076] The third condition is: heat-affected areas on the removed edge material area caused by laser removal (cutting) operations;
[0077] The fourth condition is: the second dynamic thickness difference ΔT of the battery electrode. 动 'Less than or equal to the preset dynamic thickness acceptable difference (that is, the brush roller also continues to remove the powder from the edge area of the material zone that exceeds the normal material zone thickness)'
[0078] The second dynamic thickness difference ΔT of the battery electrode 动 ', equals the edge thickness (i.e., edge thickness) of the battery electrode sheet after the powder removal operation using laser and brush rollers. 动0 'And the thickness of the normal material zone (e.g., the thickness of the middle area) T 动1 The absolute value of the difference between them;
[0079] Among them, the second dynamic thickness difference ΔT of the battery electrode 动 '=|T 动0 '-T 动1 '|.
[0080] In this invention, for specific implementation, see [link to relevant documentation]. Figure 1b As shown, after laser removal (i.e., cutting) of the powder in the edge area of the battery electrode under dynamic conditions, the powder distribution of the battery electrode is as follows. Figure 1b As shown. For the edge material area after laser cleaning, its upper part is similar to a crescent shape, and the central area has less material powder. The cleaning depth of the central area irradiated by the laser is deeper than that of the two sides.
[0081] In this invention, specifically, the preset dynamic thickness acceptable difference value ranges from 0 to 3 μm, preferably 3 μm or 2 μm.
[0082] In this invention, it should be noted that during the laser removal (cutting) of the edge material area of the battery electrode, the powder area near the cut is heated, which may cause changes in the powder structure, forming a heat-affected zone (i.e., a heat-affected area). The presence of the heat-affected zone affects the smoothness of the surface of the edge material area of the battery electrode, and may even cause phenomena such as indentation. Therefore, it is necessary to further employ a brush roller to continue the powder removal operation to remove the heat-affected zone (i.e., the heat-affected area) formed on the battery electrode due to the laser removal operation.
[0083] It should be noted that after continuous energy input from a laser to the edge material area of the battery electrode, significant heat accumulation will occur, forming a heat-affected zone. In this case, it is necessary to remove the heat-affected zone using a brush roller.
[0084] In this invention, specifically in step S22, when the laser is used to remove (i.e., cut) the powder in the edge area of the battery electrode sheet under dynamic conditions, the thickness of the powder removed by the laser ranges from 20% to 60% ΔT.动 In other words, the height of the edge material area removed by laser is 20%-60% of the thickness of the extra-thick portion of the edge material area.
[0085] In specific implementation, in step S22, the thickness of the powder eliminated by the brush roller ranges from 40% to 80% ΔT. 动 .
[0086] Similarly, it should be noted that the reason why the laser cleaning thickness (i.e. the thickness of the powder removed by the laser) is selected as 20%-60% for this invention is that if the laser cleaning thickness is less than 20%, it will be difficult for the brush roller to remove the remaining powder; if the cleaning thickness is greater than 60%, it will cause the laser to clean the powder too deeply in the center, resulting in point-like lithium plating in local areas of the battery electrode during charging and discharging.
[0087] It should be noted that, in this invention, the use of a brush roller to clean the powder is primarily to reduce the central impact caused by laser cleaning alone. Due to the inherent properties of the laser, the central area of the material zone at the edge of the battery electrode after laser irradiation will have a deeper cleaning depth than the sides, resulting in less powder in the central area. (See [link to previous section]). Figure 1b As shown, a laser alone cannot be used to remove excess powder. In this invention, after removing excess powder from the electrode using a brush roller, the electrode becomes flatter, avoiding the problem of insufficient powder in the central area during laser cleaning. The removal ratio of the brush roller (i.e., the thickness of powder removed by the brush roller) is mainly due to the characteristics of the brush roller. Without the initial laser cleaning to disrupt the edge powder area, the brush roller cannot remove excess powder.
[0088] It should be noted that, for this invention, when the first dynamic thickness difference ΔT of the battery electrode is large, the thickness of the part that needs to be cut off by laser is relatively large. In this case, the output power of the continuous laser used to output the laser should be increased accordingly.
[0089] In this invention, specifically in step S22, the second dynamic thickness difference ΔT of the battery electrode is... 动 ≤3μm.
[0090] In this invention, specifically in step S22, if the second dynamic thickness difference ΔT of the battery electrode sheet... 动 If a preset dynamic thickness acceptable difference (e.g., 3μm) is set, the pressure applied by the brush roller to the battery electrode is increased (e.g., vertical downward pressure applied to the battery electrode directly below), and the gap between the brush roller body (with bristles evenly distributed on it) and the surface of the battery electrode is reduced (i.e., the spacing) until the battery electrode simultaneously meets the third and fourth conditions.
[0091] It should be noted that when the battery electrode is in a dynamic state, for the battery electrode after the cleaning operation, if the thickness difference between the edge and the center (the second dynamic thickness difference value ΔT of the battery electrode) is... 动 If the preset dynamic thickness acceptable difference (e.g., 3μm) is greater than the required value, it indicates that the edge removal ability is insufficient. It is necessary to further increase the pressure between the brush roller and the electrode and reduce the gap between the brush roller body (with bristles evenly distributed on the roller body) and the surface of the battery electrode. The purpose is to further increase the brush roller's ability to remove powder from the material area.
[0092] In summary, this invention uses an electrode thickness detection mechanism (e.g., a micrometer or an infrared detector) to detect the overall thickness of the coated and dried electrode, determining the difference between the thickness of the edge material area (i.e., edge thickness) and the thickness of the normal material area (e.g., the thickness of the central area). Then, a laser is used to pre-remove the excessively thick parts in the edge material area (typically, the height of the laser-removed material area is equal to 20%-60% of the thickness ΔT of the excessively thick part of the edge material area). After laser removal, the battery electrode is then subjected to rapid rotation and friction with a brush roller to further remove the heat-affected areas formed by the laser removal operation, ensuring that the edge surface density of the battery electrode is maintained while removing the excessively thick parts of the edge material area.
[0093] In this invention, the laser power output by the continuous laser and the pressure and gap of the brush roller are adjusted in a closed loop according to the thickness difference obtained by the thickness detection mechanism. While eliminating excess powder and reducing the thickness of the material area at the edge of the battery electrode, the edge surface density of the battery electrode is guaranteed, thereby effectively avoiding a series of problems caused by excessive thickness of the electrode edge.
[0094] To better understand the technical solution of the present invention, specific embodiments are provided below to illustrate the technical solution of the present invention. Unlike existing conventional technologies, the method for optimizing the edge thickness of battery electrode sheets provided by the present invention is a method for eliminating thick edges of coated electrode sheets. This method mainly involves targeted removal of excessively thick areas at the edge of the electrode sheet after coating and drying. This can solve the problem of excessively thick electrode sheet edges (i.e., excessive thickness) while ensuring the consistency of the overall electrode sheet surface density.
[0095] Example 1.
[0096] Select battery electrode sheets (positive or negative). The current collector of the battery electrode sample should be 3.5-8 μm thick, and the slurry coating width on the surface of the current collector should be 280-310 mm. The single-sided areal density of the slurry coating should be 12.12 mg / cm³. 2 The coating method adopted is continuous coating.
[0097] In practical implementation, when the battery electrode is a negative electrode, the current collector is copper foil, and the negative electrode slurry is an aqueous slurry. The negative electrode active material can be graphite, hard carbon, or silicon; the conductive agent is SP or carbon nanotubes, etc.; the dispersant is CMC or PAA-type adhesive, etc.; and the binder is PVDF or SBR. The negative electrode slurry is obtained by mixing the active material (main material) at a mass percentage of 93-97.5%, the conductive agent at 0.5-5%, the dispersant at 0.9-2%, and the binder at 1.1-1.5%.
[0098] When the battery electrode is a positive electrode, the current collector is aluminum foil, and the positive electrode active material can be lithium cobalt oxide, ternary (nickel cobalt manganese oxide) or lithium iron phosphate; the conductive agent is SP or carbon nanotubes, etc.; the dispersant is CMC or PAA-type adhesive, etc.; and the binder is PVDF or SBR. The positive electrode slurry is obtained by mixing the main active material (93-97.5%), conductive agent (0.5-5%), dispersant (0.9-2%), and binder (1.1-1.5%) by mass percentage.
[0099] For the battery electrode sheets obtained by the above continuous coating method, based on the technical solution of the present invention, the following processing steps can be performed:
[0100] Step 1: After coating and drying, the battery electrode sheets are sampled in segments to obtain 10 battery electrode sheet samples of the same length. The thickness of the normal material area (e.g., the thickness of the middle area) and the thickness of the edge material area of each sample are measured.
[0101] Table 1: Schematic diagram of the edge material thickness (i.e., thickness before powder removal) of 10 battery electrode samples obtained from continuous coating.
[0102]
[0103] In Table 1 above, the leftmost column of values, 1 to 10, represents 10 battery electrode samples; the topmost column of values, 1 to 7, represents the number of thickness measurements. Averape is the average value, MAX is the maximum value, MIN is the minimum value, and "STD." is the standard deviation.
[0104] As shown in Table 1, the thickness of the normal material area of the 10 battery electrode samples was 232-234 μm after testing; the thickness of the edge of the electrode (i.e., the thickness of the edge material area) was 238-243 μm (the above thicknesses are the sum of the thickness of the powder coating on both sides and the thickness of the current collector of the electrode).
[0105] Step 2: Set the adjustable range of the powder cleaning parameters, as follows:
[0106] Output laser power of continuous laser: 2000W, power range: 0-100%; output speed of continuous laser: 10000-50000mm / s;
[0107] The gap between the brush rollers (i.e., the gap between the brush roller body and the surface of the battery electrode) is 50-400μm, the brush roller rotation speed is 10-300rpm / min, and the pressure of the brush rollers (e.g., the vertical downward pressure applied to the battery electrode directly below) is 0-20N.
[0108] Step 3: Dynamic thickness measurement. Use an infrared detection mechanism (such as an infrared detector) to perform an overall scan and thickness measurement of the electrode sheet.
[0109] Table 2: A schematic diagram showing the thickness of the edge material area (i.e., the thickness after powder removal) of 10 battery electrode samples obtained from continuous coating.
[0110]
[0111] In Table 2 above, the leftmost column of values, 1 to 10, represents 10 battery electrode samples; the topmost column of values, 1 to 7, represents the number of thickness measurements. Averape is the average value, MAX is the maximum value, MIN is the minimum value, and "STD." is the standard deviation.
[0112] As shown in Table 2, the measured thickness range of the normal material area of the 10 battery electrode samples is 232-234 μm; the thickness of the electrode edge (i.e., the thickness of the edge material area) ranges from 238 to 243 μm (the above thicknesses are the sum of the thickness of the powder coating on both sides and the thickness of the current collector of the electrode).
[0113] Step 4: Adjust the dynamic cleaning parameters, and then perform a cleaning operation on the remaining battery electrodes in the entire electrode roll (i.e., the electrode roll) where the sampled battery electrode is located (remove the difference between the thickness of the edge material area and the thickness of the normal material area of the battery electrode), so as to obtain battery electrodes with qualified edge material area thickness.
[0114] The dynamic powder cleaning parameters are as follows:
[0115] Adjust the output laser power of the continuous laser to 2000W, and adjust the output laser power range to 10%, and the powder removal width to 200μm;
[0116] The gap of the brush roller is 80μm, the speed of the brush roller is 120rpm / min, the pressure of the brush roller is 5N, and the distance between the inner side of the brush roller (i.e., the roller body) and the edge of the electrode is 2mm (the edge of the electrode refers to the junction of the material area of the electrode and the current collector foil).
[0117] Example 2.
[0118] Select battery electrode sheets (positive or negative). The current collector of the battery electrode sample should be 3.5-8 μm thick. The slurry coating width on the surface of the current collector should be 280-310 mm. The coating length on side A (e.g., the upper surface) should be 500-1500 mm, and the coating length on side B (e.g., the lower surface) should also be 500-1500 mm. The surface density of the slurry coating on one side should be 12.12 mg / cm³. 2 The coating method adopted is: intermittent coating.
[0119] In practical implementation, when the battery electrode is a negative electrode, the current collector is copper foil, and the negative electrode slurry is an aqueous slurry. The negative electrode active material can be graphite, hard carbon, or silicon; the conductive agent is SP or carbon nanotubes, etc.; the dispersant is CMC or PAA-type adhesive, etc.; and the binder is PVDF or SBR. The negative electrode slurry is obtained by mixing the active material (main material) at a mass percentage of 93-97.5%, the conductive agent at 0.5-5%, the dispersant at 0.9-2%, and the binder at 1.1-1.5%.
[0120] When the battery electrode is a positive electrode, the current collector is aluminum foil, and the positive electrode active material can be lithium cobalt oxide, ternary (nickel cobalt manganese oxide) or lithium iron phosphate; the conductive agent is SP or carbon nanotubes, etc.; the dispersant is CMC or PAA-type adhesive, etc.; and the binder is PVDF or SBR. The positive electrode slurry is obtained by mixing the main active material (93-97.5%), conductive agent (0.5-5%), dispersant (0.9-2%), and binder (1.1-1.5%) by mass percentage.
[0121] For the battery electrode sheets obtained by the above-mentioned interval coating method, based on the technical solution of the present invention, the following processing steps can be performed:
[0122] Step 1: Take samples of the coated and dried electrode sheets to obtain 5 battery electrode sheet samples of the same length. Measure the thickness of the normal material area (e.g., the thickness of the middle area) and the thickness of the first position (i.e., the thickness of the material area at the first position of the battery electrode slurry coating, which is the thickness at the front edge of the coating. At this time, the first position of the electrode slurry coating is prone to forming a semi-circular protrusion).
[0123] Table 3: A schematic diagram of the thickness of the material area at the beginning and middle positions of five battery electrode samples obtained from sampling of spaced coated battery electrodes (i.e., a schematic diagram of the thickness of the material area at the beginning position before powder removal).
[0124]
[0125] In Table 3 above, the leftmost column of values, 1 to 5, represents 5 battery electrode samples; the topmost column of values, 1 to 7, represents the number of thickness measurements. Averape is the average value, MAX is the maximum value, MIN is the minimum value, and "STD." is the standard deviation.
[0126] As shown in Table 3, after testing, the thickness range of the normal material area of the five battery electrode samples is 232-234 μm; the thickness range of the head position is 238-242 μm (the above thicknesses are the sum of the thickness of the double-sided powder and the thickness of the current collector of the electrode).
[0127] Step 2: Set the adjustable range of the powder cleaning parameters, as follows:
[0128] Output laser power of continuous laser: 2000W, power range: 0-100%; output speed of continuous laser: 10000-50000mm / s;
[0129] The gap between the brush rollers (i.e., the gap between the brush roller body and the surface of the battery electrode) is 50-400μm, the brush roller speed is 10-300rpm / min, and the brush roller pressure is 0-20N.
[0130] Step 3: Dynamic thickness measurement. Use an infrared detection mechanism (such as an infrared detector) to perform an overall scan and thickness measurement of the electrode sheet.
[0131] Table 4: Thickness of the first and middle material areas of five battery electrode samples obtained by sampling the spaced-coated battery electrodes after de-powdering (i.e., the thickness after de-powdering).
[0132]
[0133] In Table 4 above, the leftmost column of values, 1 to 5, represents 5 battery electrode samples; the topmost column of values, 1 to 7, represents the number of thickness measurements. Averape is the average value, MAX is the maximum value, MIN is the minimum value, and "STD." is the standard deviation.
[0134] As shown in Table 4, the normal material area thickness of the five battery electrode samples was measured to be 232-234 μm; the edge thickness (i.e., the edge material area thickness, which is the material area at the beginning position) was 238-243 μm (the above thicknesses are the sum of the thickness of the powder coating on both sides and the current collector thickness of the electrode).
[0135] Step 4: Adjust the dynamic cleaning parameters, and then perform a cleaning operation on the remaining battery electrodes in the entire electrode roll (i.e., the electrode roll) where the sampled battery electrode is located (remove the difference between the thickness of the edge material area and the thickness of the normal material area of the battery electrode, at this time the edge material area is the first position material area), so as to obtain battery electrodes with qualified edge material area thickness.
[0136] The dynamic powder cleaning parameters are as follows:
[0137] Adjust the output laser power of the continuous laser to 2000W, and adjust the output laser power range to 10%, the beam emission speed to 20000mm / s, and the powder removal width to 200μm;
[0138] Brush roller gap: 80μm, brush roller speed: 120rpm / min, brush roller pressure: 5N, the distance between the inner side of the brush roller (i.e., the roller body) and the edge of the electrode sheet is 2mm (the edge of the electrode sheet refers to the junction between the electrode sheet material area and the foil material).
[0139] In embodiments 1 and 2 above, the powder removal parameters are specific values used to achieve the actual effect or the inherent capabilities of existing equipment. Therefore, the scope of protection for this part should be expanded. For example, the laser source power used in the embodiments is 2000W, and the scope of protection should not be limited to laser sources of 2000W, etc.
[0140] In summary, the optimized edge thickness processing method for battery electrode sheets provided by this invention is a novel approach to solving the problem of thick edges in coating, differing from traditional methods that suppress thick edges during the coating stage. This invention uses lasers and brush rollers to perform targeted powder removal at excessively thick edges of the electrode sheet after coating and drying, ensuring both the elimination of abnormally thick edges and the consistency of the overall surface density of the electrode sheet.
[0141] In this invention, after the battery electrode is coated and dried, a continuous laser is used to pre-remove the ultra-thick parts of the electrode, and then a brush roller is used to remove the heat-affected part and the electrode powder in the ultra-thick parts of the electrode.
[0142] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for optimizing the edge thickness of battery electrode sheets, characterized in that, Includes the following steps: Step S1, test the thickness difference of the battery electrode: For the battery electrode after the slurry coating and drying are completed, test the thickness of the edge material area and the thickness of the normal material area of the battery electrode to obtain the thickness difference of the battery electrode. Step S2, perform powder removal operation on the battery electrode sheet: First, use a laser to remove the powder from the edge area of the battery electrode sheet. Then, use a rotating brush roller to rub the edge area of the battery electrode sheet to continue removing the powder from the edge area, so as to obtain a battery electrode sheet with qualified edge thickness.
2. The method for optimizing the edge thickness of battery electrode sheets as described in claim 1, characterized in that, For battery electrodes obtained by continuous coating, the edge material area of the battery electrode is the material area on the left and right edges of the battery electrode slurry coating. For battery electrodes obtained by intermittent coating, the edge material area of the battery electrode is the material area at the beginning of the battery electrode slurry coating.
3. The method for optimizing the edge thickness of battery electrode sheets as described in claim 1, characterized in that, The laser is a continuous laser output from a continuous laser (5).
4. The method for optimizing the edge thickness of battery electrode sheets as described in claim 1, characterized in that, For battery electrode sheets obtained by continuous coating, two continuous lasers (5) are set directly above the edge material areas on the left and right sides of the battery electrode sheet; A brush roller (6) is provided directly above the battery electrode.
5. The method for optimizing the edge thickness of battery electrode sheets as described in claim 1, characterized in that, When the battery electrode is in a static state, step S1 specifically includes the following step S11, and step S2 specifically includes the following step S12. Step S11, test the static thickness difference of the battery electrode: For the battery electrode in a static state after the slurry coating and drying are completed, test the thickness of the edge material area and the thickness of the normal material area of the battery electrode to obtain the first static thickness difference ΔT of the battery electrode. Step S12, static material powder removal operation of battery electrode sheet: First, the material powder in the edge area of the battery electrode sheet in a static state is removed by laser. Then, the edge area of the battery electrode sheet is rubbed by rotating brush roller to continue the material powder removal operation in the edge area of the battery electrode sheet until the battery electrode sheet meets the first condition and the second condition at the same time, so as to obtain a battery electrode sheet with qualified edge material area thickness. The first condition is: the heat-affected areas on the edge material area that have been removed due to the laser cleaning operation; The second condition is: the second static thickness difference ΔT' of the battery electrode is less than or equal to the preset static thickness acceptable difference; The second static thickness difference ΔT' of the battery electrode is equal to the absolute value of the difference between the edge material area thickness T0' and the normal material area thickness T1' of the battery electrode after the material powder removal operation by laser and brush roller. Among them, the second static thickness difference of the battery electrode is ΔT'=|T0'-T1'|.
6. The method for optimizing the edge thickness of battery electrode sheets as described in claim 5, characterized in that, In step S11, for the battery electrode sheet after the slurry coating and drying are completed, when it is in a static state, the static thickness of the battery electrode sheet is measured using a micrometer. The thickness of the edge material area T0 and the thickness of the normal material area T1 of the battery electrode sheet are measured before the powder removal operation. The first static thickness difference of the battery electrode sheet, ΔT = T0 - T1, is the thickness of the powder material on the battery electrode sheet that needs to be removed.
7. The method for optimizing the edge thickness of battery electrode sheets as described in claim 5, characterized in that, In step S12, when the laser is used to remove the powder from the edge area of the battery electrode in a static state, the thickness of the powder removed by the laser ranges from 20% to 60%ΔT. And / or, In step S12, the thickness of the powder eliminated by the brush roller ranges from 40% to 80% ΔT; And / or, In step S12, if the second static thickness difference ΔT' of the battery electrode is greater than the preset static thickness acceptable difference, the pressure applied by the brush roller to the battery electrode is increased, and the gap between the brush roller body and the surface of the battery electrode is reduced, until the battery electrode simultaneously meets the first condition and the second condition.
8. The method for optimizing the edge thickness of battery electrode sheets as described in claim 1, characterized in that, When the battery electrode is in a dynamic state, step S1 specifically includes the following step S21, and step S2 specifically includes the following step S22. Step S21, test the dynamic thickness difference of the battery electrode: For the battery electrode under dynamic conditions after slurry coating and drying, test the thickness of the edge material area and the normal material area of the battery electrode to obtain the first dynamic thickness difference ΔT of the battery electrode. 动 ; Step S22, perform dynamic powder removal operation on the battery electrode sheet: First, use a laser to remove the powder from the edge area of the battery electrode sheet under dynamic conditions. Then, use a rotating brush roller to rub the edge area of the battery electrode sheet to continue removing the powder from the edge area of the battery electrode sheet until the battery electrode sheet meets the third and fourth conditions at the same time, thereby obtaining a battery electrode sheet with qualified edge area thickness. The third condition is: heat-affected areas on the removed edge material area caused by the laser removal operation; The fourth condition is: the second dynamic thickness difference ΔT of the battery electrode. 动 'Less than or equal to the preset dynamic thickness acceptable difference;' The second dynamic thickness difference ΔT of the battery electrode 动 ', which is equivalent to the thickness T of the edge material area of the battery electrode after the material powder removal operation by laser and brush roller. 动0 'and normal material zone thickness T 动1 The absolute value of the difference between them; Among them, the second dynamic thickness difference ΔT of the battery electrode 动 '=|T 动0 '-T 动1 '|.
9. The method for optimizing the edge thickness of battery electrode sheets as described in claim 1, characterized in that, In step S21, for the battery electrode sheet after slurry coating and drying, when it is in a dynamic state, an infrared detector is used to perform static thickness measurement on the battery electrode sheet, and the thickness T of the edge material area of the battery electrode sheet is measured before the powder removal operation. 动0 and normal material zone thickness T 动1 ; Among them, the first dynamic thickness difference ΔT of the battery electrode 动 =T 动0 -T 动1 This refers to the thickness of the powder material on the battery electrode that needs to be removed. And / or, In step S22, when the laser is used to remove the powder from the edge area of the battery electrode under dynamic conditions, the thickness of the powder removed by the laser ranges from 20% to 60% ΔT. 动 ; And / or, In step S22, if the second dynamic thickness difference ΔT of the battery electrode is... 动 If a preset dynamic thickness acceptable difference is set, the pressure applied by the brush roller to the battery electrode will be increased, and the gap between the brush roller body and the surface of the battery electrode will be reduced until the battery electrode simultaneously meets the third and fourth conditions.
10. The method for optimizing the edge thickness of battery electrode sheets as described in claim 9, characterized in that, For continuously coated battery electrodes, an infrared detector (4) is placed directly above the lateral center of the battery electrode. Two additional infrared detectors (4) are installed directly above the edge material areas on the left and right sides of the battery electrode.